Relationship between polymorphisms in −572G/C interleukin 6 promoter gene polymorphisms (rs1800796) and risk of rheumatoid arthritis: A meta‐analysis. (29th November 2019) - Zhang, Chunfang; Jiao, Shuang; Li, Tianyu; Zhao, Lihua; Chen, Huijun
Abstract: Aims: This meta‐analysis was aimed to investigate the association between −572G/C interleukin (IL)‐6 gene polymorphism and occurrence risk of rheumatoid arthritis (RA). Methods: Literature search was conducted in PubMed, Embase, Springer and Google Scholar up to November 2018. The pooled odds ratios (ORs) and 95% confidence interval (CI) were calculated by Revman 5.3. Results: A total of six case‐control studies were included in this meta‐analysis. In the allele model (G vs C), homozygous gene model (GG vs CC), recessive gene model (GG vs GC + CC), and dominant gene model (GG + GC vs CC), the pooled estimate indicated there was significant association between −572G/C IL‐6 gene polymorphism and risk of RA. However, no significant statistical results were found in meta‐analyses of heterozygote gene models. Conclusions: The −572G/C IL‐6 gene polymorphism is associated with the risk of RA. The GG genotype may be the main contributor in increasing susceptibility to RA.